Evaluation of a high-EPA oil from transgenic Camelina sativa in feeds for Atlantic salmon (Salmo salar L.): Effects on tissue fatty acid composition, histology and gene expression - Betancor, M.B. (Aquaculture, 2015)
Currently, one alternative for dietary fish oil (FO) in aquafeeds is vegetable oils (VO) that are devoid of omega-3 (n-3) long-chain polyunsaturated fatty acids (LC-PUFAs). Entirely new sources of n-3 LC-PUFA such as eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids through de novo production are a potential solution to fill the gap between supply and demand of these important nutrients. Camelina sativa was metabolically engineered to produce a seed oil (ECO) with > 20% EPA and its potential to substitute for FO in Atlantic salmon feeds was tested. Fish were fed with one of the three experimental diets containing FO, wild-type camelina oil (WCO) or ECO as the sole lipid sources for 7 weeks. Inclusion of ECO did not affect any of the performance parameters studied and enhanced apparent digestibility of individual n-6 and n-3 PUFA compared to dietary WCO. High levels of EPA were maintained in brain, liver and intestine (pyloric caeca), and levels of DPA and DHA were increased in liver and intestine of fish fed ECO compared to fish fed WCO likely due to increased LC-PUFA biosynthesis based on up-regulation of the genes. Fish fed ECO showed slight lipid accumulation within hepatocytes similar to that with WCO, although not significantly different to fish fed FO. The regulation of a small number of genes could be attributed to the specific effect of ECO (311 features) with metabolism being the most affected category. The EPA oil from transgenic Camelina (ECO) could be used as a substitute for FO, however it is a hybrid oil containing both FO (EPA) and VO (18:2n-6) fatty acid signatures that resulted in similarly mixed metabolic and physiological responses.